A matter of taste: Qi (vital energy) and the tending of the heart (xin) in Mencius 2A2 - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2002)
MENCIUS2A2 offers an intriguing account of the relationship between the “heart” (xin) and qi — the “vital energy” that engenders and sustains life — and their role in self-cultivation. On the one hand, it portrays an ethical ideal marked by a heart — or “heart-mind,” as some translators prefer, taking into consideration both the affective and cognitive concerns that the concept of xin encompasses — that is firm and unwavering in its aims and direction. The assumption seems to be that qi acts as an unruly or prejudicial influence that would disturb the heart and, as such, must be tightly controlled and made to serve moral ends. On the other hand, the Mencius also discloses that a “floodlike qi” (haoranzhiqi) informs the ethically accomplished person. How is this different from qi, which presumably is not “floodlike” for most people, and how can it be attained? Is it the case that when the heart is ethically determined, qi would become “floodlike”? In this essay, I propose to examine Mencius2A2 afresh, building on the works of D. C. Lau, David Nivison, Jeffrey Riegel, Kwong-Loi Shun, and others, and in the light of some of the recently discovered Guodian texts. While the concept of qi is generally recognized to have an important role in Mencian ethics, the question remains whether it is viewed as a negative or positive influence and consequently how it relates to the process of self-cultivation. It is my submission that Mencius shared with his contemporaries a basic understanding of qi as constitutive of the person, but he differed from them in locating in it a source of moral excellence.